Assessment of suitability of mangrove wood for different uses - Madson L. Galvão; João R. C. Nobre; Bruno M. Balboni; Iedo S. Santos; Marcus E. B. Fernandes (Journal of Wood Science)
Abstract This study analyzes the suitability of wood from tree species in Amazonian mangroves using secondary data on their chemical, physical, and mechanical properties. Mangrove species are Rhizophora mangle (red mangrove), Avicennia germinans (black mangrove), and Laguncularia racemosa (white mangrove). Rhizophora mangle stood out regarding chemical, physical, and mechanical properties, being suitable for charcoal production and civil construction due to its low ash content (0.8%) and high lignin content (24.9%). Physical and mechanical analyses confirm the high density and resistance of R. mangle (ρ = 0.83 g cm−3; ρ 12%  = 1031.6 kg m−3), while A. germinans and L. racemosa, although suitable, present some limitations. When evaluating the wood quality, the correlation matrix shows a strong correlation between the physical and mechanical properties of the mangrove tree species. More in-depth studies on the anatomy and durability of these woods are still necessary to optimize their use and conservation. The results presented here are crucial to support management and conservation policies for forest resources in mangroves on the Brazilian Amazon coast.